Characterisation of the C50 carotenoids produced by strains of the cheese-ripening bacterium Arthrobacter arilaitensis. (April 2016) - Giuffrida, Daniele; Sutthiwong, Nuthathai; Dugo, Paola; Donato, Paola; Cacciola, Francesco; Girard-Valenciennes, Emmanuelle; Le Mao, Yves; Monnet, Christophe; Fouillaud, Mireille; Caro, Yanis; Dufossé, Laurent
Abstract: Pigments were extracted from cheese-ripening bacteria belonging to the species Arthrobacter arilaitensis, which plays a role in the colour of cheese. A chromatographic method was applied to characterise the pigment profile. Based on the UV–visible (UV–vis) spectra, the mass spectra, and the elution order, eight different carotenoids were identified from the strains. Four of the pigments, namely, all- E -decaprenoxanthin, all- E -sarcinaxanthin, 9- Z -decaprenoxanthin and 15- Z -decaprenoxanthin, which were present as free-form main carotenoids (i.e., non-glycosylated), have been characterised by their UV–vis and mass spectra, both in atmospheric-pressure chemical ionisation negative [APCI (−)] and positive modes. The other minor carotenoids, namely, sarcinaxanthin monoglucoside pentaacetate, decaprenoxanthin monoglucoside, decaprenoxanthin diglucoside, decaprenoxanthin-C16:0 (decaprenoxanthin-palmitate), present in very low amounts, were only detected in the APCI (−) ionisation mode. Our results provide the first chemical characterisation of the pigments produced by cheese-ripening A. arilaitensis strains, which has not previously been reported.